2013
DOI: 10.5539/jsd.v6n12p111
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Approach to Riparian-Buffer Definition, and Implications for Timber Harvests in Nova Scotia, Canada

Abstract: Riparian buffers in North America usually have been designed to mitigate specific land-use impacts on watercourses, and thus often fail to preserve the full range of riparian ecological functions (e.g. wildlife habitat). This paper reviews the unique ecological characteristics of riparian areas in an attempt to formulate a widely applicable buffer delineation capable of maintaining most riparian ecosystem services. To avoid ambiguity, the watercourse is defined in terms of its high water mark, which includes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 108 publications
(174 reference statements)
1
7
0
Order By: Relevance
“…It is understandable that concerns exist among land-use managers about the extent of resources that might be "locked up" in such buffer strip reserves. However, several Canadian GIS studies have shown that these concerns may be exaggerated, at least for non-mountainous areas [15] [26]. The present study suggests that expanding protective buffer strips from the legal requirement of 30 m to an increased width of 70 m will be needed in order to offset projected increases of 25% in soil erosion due to regional climate change over the next half century.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…It is understandable that concerns exist among land-use managers about the extent of resources that might be "locked up" in such buffer strip reserves. However, several Canadian GIS studies have shown that these concerns may be exaggerated, at least for non-mountainous areas [15] [26]. The present study suggests that expanding protective buffer strips from the legal requirement of 30 m to an increased width of 70 m will be needed in order to offset projected increases of 25% in soil erosion due to regional climate change over the next half century.…”
Section: Discussionmentioning
confidence: 70%
“…Few BMPs deliver more ecosystem goods and services per unit areal coverage than do riparian buffer strips [13] [14], particularly in relation to reducing the transport and deposition of soil to otherwise threatened lakes and rivers, such as those in Canada [10] [26]. In a comprehensive review, Capron et al [27] identify riparian ecosystems as being those landscapes that will be in particular need for adapting human activities in the face of climate change.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delineating riparian areas may assist in improving our understanding of how these areas might benefit ecosystem service provision by (a) identifying patterns in land use and their importance in the landscape, (b) characterizing soil types and habitat distributions within the riparian areas, (c) reducing the anthropogenic pressures to which they are subject, (d) preserving their intrinsic value, and (e) establishing a common framework for their classification. Numerous approaches to delineate riparian areas have been undertaken ranging from simplistic models in which a fixed‐width buffer is implemented (Hawes & Smith, ; Stoffyn‐Egli & Duinker, ), to more complex holistic approaches where the most relevant riparian characteristics such as soil properties, associated floodplain extent, vegetation type, or hydrologic parameters are integrated into delineation models of varying complexity. These are subsequently used to generate a variable‐width riparian buffer (Abood & Maclean, ; Baker, Lawrence, Montagne, & Patten, ; Belletti et al, ; Lyons, Görres, & Amador, ; Momm & Bingner, ).…”
Section: Introductionmentioning
confidence: 99%